PENGARUH SUMBER BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MTsN 8 HULU SUNGAI UTARA - Hamidah, Hamidah; Syahrani, Syahrani; Dzaky, Ahmad (FIKRUNA Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2023)
The ultimate goal of learning activities is to achieve good goals or learning outcomes and achieving them is not as easy as expected, there are many influencing factors, including learning resources. This study aims to determine the effect of learning resources on student learning outcomes in the Akidah Akhlak subject at MTsN 8 Hulu Sungai Utara. Data collection techniques in this study used interviews, observation, questionnaires and documentaries. Data is processed using editing, coding, scoring, tabulation and data interpretation techniques, then data analysis is carried out. The results of this study are the effect of learning resources on student learning outcomes in the Akidah Akhlak subject at MTsN 8 Hulu Sungai Utara of 0.190, which is in the interval 0.00 - 0.20 with the interpretation between variable X and variable Y there is a correlation, however the correlation is very weak or very low, so the correlation is ignored. Thus, there is no influence between learning resources on student learning outcomes in the Aqidah Akhlak subject at MTsN 8 Hulu Sungai Utara, this is because the rxy value (0.190) is less than the rt level of 5% (0.304) or rt level of 1% (0.393), so (Ha) is rejected and (Ho) is accepted.